Between the Fantastic and the Mystical: The Mysterious - Olivé Ràfols, Laia (2022)
Though differently, the fantastic and the mystical approach the mystery, which is the unknown that causes both fear and desire. This article reviews their approach and its common terminology in research about both the fantastic and the mystical aiming to propose an in-between phenomenon, which is present in lyrical poetry: “the mysterious”. The fantastic deals with the unknown through fictitious narration by means of extraordinary events that belong to another world, that take place in the intratextual reality (reflect of the reader’s reality) and that provoke an “estrangement”. For its part, the mystical tries to describe the indescribable divine union experienced by the mystic through the language that is closest to abstraction due to its musicality and that is exempt from fictionality thanks to its emotionality, that is to say, lyrical poetry. The mysterious shares some of these characteristics and is the treatment of the secret in our world through modern lyric. The article provides some extracts from the short story “El perseguidor” (1986) by Cortázar for the fantastic, from poems by San Juan de la Cruz for the mystical and the poem “Al centro rayeante” (1949) by Juan Ramón Jiménez for the mysterious.